Shifting the paradigm: reevaluating resistance to organizational change. Issue 6 (3rd October 2016) - Mathews, Brandon; Linski, Christopher M.
Abstract : Purpose: The purpose of this paper is to challenge the existing paradigm of resistance to organizational change by offering a novel, interdisciplinary perspective. More specifically, this paper seeks to detach from traditional formulations of resistance to change and introduce a new paradigm, reevaluating resistance through the Good Lives Model (GLM) and the concept of Primary Human Goods (PHG). Design/methodology/approach: This conceptual paper uses contemporary literature on resistance to organizational change to make the case that the existing paradigm is one of negativity and deficiency. The authors define resistance, as currently formulated, subsequently offering a new perspective through the GLM. The etiological underpinnings of the model are provided and the concept of PHG is defined to illustrate relevance in reevaluating resistance to change. Findings: The paper illustrates that resistance behaviors are not individual problems of employees, which must be overcome for successful change. Rather, resistance behaviors are the manifestation of disruptions to the achievement of PHG. Moreover, the paper demonstrates the pursuit of PHG is an innately positive, human activity that change strategies should take into account. The Dialogic Organization Development approach is also integrated as a means to uncover priority goods and disruptions that may impact them. Originality/value: The paper provides a novel reevaluation of resistance to change through the interdisciplinary application of the GLM and PHG. Further, the paper uses the model to integrate several fundamental theories of human motivation into one cohesive, consistent framework.